Large-scale characterization of the microvascular geometry in development and disease by tissue clearing and quantitative ultramicroscopy - Hahn, Artur; Krüwel-Bode, Julia; Alexander, Allen; Karimian-Jazi, Kianush; Schregel, Katharina; Schwarz, Daniel; Sommerkamp, Alexander C.; Krüwel, Thomas; Abdollahi, Amir; Wick, Wolfgang; Platten, Michael; Bendszus, Martin; et al. (Journal of cerebral blood flow & metabolism, 2021)
Three-dimensional assessment of optically cleared, entire organs and organisms has recently become possible by tissue clearing and selective plane illumination microscopy (“ultramicroscopy”). Resulting datasets can be highly complex, encompass over a thousand images with millions of objects and data of several gigabytes per acquisition. This constitutes a major challenge for quantitative analysis. We have developed post-processing tools to quantify millions of microvessels and their distribution in three-dimensional datasets from ultramicroscopy and demonstrate the capabilities of our pipeline within entire mouse brains and embryos. Using our developed acquisition, segmentation, and analysis platform, we quantify physiological vascular networks in development and the healthy brain. We compare various geometric vessel parameters (e.g. vessel density, radius, tortuosity) in the embryonic spinal cord and brain as well as in different brain regions (basal ganglia, corpus callosum, cortex). White matter tract structures (corpus callosum, spinal cord) showed lower microvascular branch densities and longer vessel branch length compared to grey matter (cortex, basal ganglia). Furthermore, we assess tumor neoangiogenesis in a mouse glioma model to compare tumor core and tumor border. The developed methodology allows rapid quantification of three-dimensional datasets by semi-automated segmentation of fluorescently labeled objects with conventional computer hardware. Our approach can aid preclinical investigations and paves the way towards “quantitative ultramicroscopy”.
First Published October 12, 2020
Gesehen am 06.08.2021